Pengaruh Tiktok Live shopping, Consumer rating Terhadap Keputusan Pembelian dan Kepercayaan Pelanggan Sebagai Variabel Intervening (Studi pada Mahasiswa UNISMA Pengguna Aplikasi Tiktok Angkatan 2021) - Chalingga, Dicky; Widarko, Agus; Dianawati, Eris (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of TikTok Live shopping and Consumer rating on Purchase Decisions, with Customer Trust as a mediating variable. The research subjects were active students of the Islamic University of Malang (UNISMA) from the 2021 cohort who use the TikTok application and have made purchases through the TikTok Live shopping feature. A sample of 80 respondents was selected using purposive sampling. This study employed a quantitative approach with explanatory research design and path analysis to examine the relationships between variables. The findings indicate that TikTok Live shopping (X1) and Consumer rating(X2) have a positive and significant influence on Customer Trust(Z) and Purchase Decisions(Y). Moreover, Customer Trust is proven to mediate the influence of the independent variables on Purchase Decisions. These results reinforce the importance of trust as a key factor in shaping consumer decisions on digital platforms. Keywords: TikTok Live shopping, Consumer rating, Customer Trust, Purchase Decision